Activating STEAM Learning in Young Children Through Aha-Experiences: Supporting Creativity and Aesthetic Sensitivity in Infants and Toddlers - Kanako Tsuchiya; Ikuko Gyobu (Education Sciences, 2025)
This research explored the occurrence of aha-experiences in young children during participatory creative processes within STEAM learning. The study aimed to provide a comprehensive understanding of the specific conditions that contribute to the emergence of these aha-experiences. A series of activities were designed and implemented as part of a participatory observation study at the Municipal Center for Early Childhood Education and Care in Tokyo, Japan. The STEAM sessions involved the use of a Wind Tunnel and colorful scarves, engaging infants and toddlers in exploratory interactions with the device and materials alongside their classmates, teachers, and the first author, referred to as researcher T. Through video recordings, the researchers conducted microanalysis of the collected data. The findings confirmed that children’s aesthetic sensitivity was activated during aha-experiences. Furthermore, this heightened sensitivity encouraged active participation from their teachers in the creative process. The study employed a socio-cultural approach to creativity theory to interpret these aha-experiences in the context of STEAM learning. It highlighted the participatory nature of creativity and the role of aesthetic sensitivity in young children’s learning. Additionally, the study provided insights for educators and caregivers on how to support the development of creativity in infants and toddlers within STEAM learning environments.